2022
DOI: 10.3390/mi13050784
|View full text |Cite
|
Sign up to set email alerts
|

Wearable Near-Field Communication Sensors for Healthcare: Materials, Fabrication and Application

Abstract: The wearable device industry is on the rise, with technology applications ranging from wireless communication technologies to the Internet of Things. However, most of the wearable sensors currently on the market are expensive, rigid and bulky, leading to poor data accuracy and uncomfortable wearing experiences. Near-field communication sensors are low-cost, easy-to-manufacture wireless communication technologies that are widely used in many fields, especially in the field of wearable electronic devices. The in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 126 publications
0
7
0
Order By: Relevance
“…Rapid qualitative analysis (RQA) was conducted to assess the interview responses effectively and efficiently to identify major themes [58]. Codes and themes for the RQA were deductively developed based on the TAM framework and the study objective.…”
Section: Analysis For User Acceptabilitymentioning
confidence: 99%
“…Rapid qualitative analysis (RQA) was conducted to assess the interview responses effectively and efficiently to identify major themes [58]. Codes and themes for the RQA were deductively developed based on the TAM framework and the study objective.…”
Section: Analysis For User Acceptabilitymentioning
confidence: 99%
“…A study by Teller and Stivoric [ 21 ], carried out in 2004, has shown how technology may be placed into clothing or accessories such as bracelets and watches to assess, record, and relay various vital indicators. A study on situation awareness by AAL technology relies on machine-to-machine (M2M) technology [ 22 , 23 ]. It provides the adaptability needed by intelligent homes to help elderly citizens.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Thoughtful material selection and the exploration of diverse structures contribute to the sensor's heightened reliability, selectivity, and rapid response and recovery performance to external stimuli [31][32][33][34][35]. Utilizing various materials in the fabrication of RFID sensor components allows for the effective integration of RFID wireless communication technology and sensing capabilities [36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%